2020
DOI: 10.1186/s12889-020-8174-2
|View full text |Cite
|
Sign up to set email alerts
|

Store and neighborhood differences in retailer compliance with a local staple foods ordinance

Abstract: Background: Policies to improve healthy food retail have been recognized as a potential means of reducing dietrelated health disparities. The revised 2014 Minneapolis Staple Foods Ordinance instituted minimum stocking standards for healthy, staple foods. The objective of this study was to examine retailer compliance with the policy, and whether compliance varied by neighborhood and store characteristics. Methods: In this natural experiment, audits were conducted annually pre-and post-ordinance (2014-2017) in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Together, these findings could suggest that a simple policy, such as the Minneapolis ordinance, may not be sufficient to improve the availability of fruits and vegetables in small food retailers, particularly over this relatively short study period. Policy approaches recommended by the World Health Organization and others [ 32 , 33 ], coupled with the findings from this and other work [ 9 , 23 ], suggest more comprehensive strategies may be necessary to improve the healthfulness of retail settings. Promising additional strategies include things like incentivizing retailers and facilitating product distribution.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Together, these findings could suggest that a simple policy, such as the Minneapolis ordinance, may not be sufficient to improve the availability of fruits and vegetables in small food retailers, particularly over this relatively short study period. Policy approaches recommended by the World Health Organization and others [ 32 , 33 ], coupled with the findings from this and other work [ 9 , 23 ], suggest more comprehensive strategies may be necessary to improve the healthfulness of retail settings. Promising additional strategies include things like incentivizing retailers and facilitating product distribution.…”
Section: Discussionmentioning
confidence: 72%
“…Store census tracts were classified into low SES or higher SES, regardless of the city in which they were located. Following our prior work [ 23 ], we defined low SES as census tracts with >50% of residents at or below 185% of the U.S. federal poverty level, based on household income and size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Store stocking requirements [ 51 ] are a potential policy lever to increase the ratio of healthful to unhealthful foods (e.g., eligibility criteria for stores to accept SNAP or local ordinances). However, a recent evaluation of the Minneapolis Staple Food Ordinance found that corporate-owned stores made greater gains in complying with healthy stocking requirements compared to independently owned stores [ 52 ]. Therefore, such requirements should be coupled with financing initiatives [ 53 , 54 ] to help independently owned stores stock healthy foods (e.g., refrigerated storage) and community engagement to increase demand for healthy foods to support the commercial viability of such efforts [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, ownership at sources, such as grocery stores and supermarkets, remains relatively diverse; though, these also show growing declines in the presence (number and market share) of independent ownership [ 60 ]. With these shifts in centralizing ownership to fewer hands, much remains to be investigated and understood about how these different ownership types and business models contribute to the RFE [ 63 , 64 ].…”
Section: Retail Food Environmentmentioning
confidence: 99%